Effect of Technology Self-Efficacy on The Relationship of Innovative Learning Skills and Learning Sustainability Among UAE Students - Mubarak, Zainab Khaflan; Selimin, Mohamad Ali (International Journal of Sustainable Construction Engineering and Technology, 2024)
Amid the rapid adoption of Education 4.0 and the widespread shift to online learning in education, there is a critical concern about the readiness of high school students to navigate sustainable e-learning, prompting a study to investigate how Education 4.0's innovative learning skills affect their learning sustainability in the UAE and contribute valuable data for informed educational strategies. This research explores the inherent innovative learning skills of Education 4.0 and their influence on the sustainable acquisition of knowledge among high school students in the UAE. It examines the prevalent innovative learning skills, scrutinizes their impact on learning sustainability, and investigates the potential mediating role of technology self-efficacy in this dynamic. The study utilized a quantitative methodology, gathering data through distributed questionnaires among a selected group of 384 high school students in Abu Dhabi, UAE. The data was utilized to construct a mediation model exploring how Technology Self-Efficacy influences the relationship between Innovative Learning Skills and Learning Sustainability in UAE students. The analysis on the model found that the Technology Self-Efficacy has four partial mediation effects and one full mediation effect on the relationship between Innovative Learning Skills and Learning Sustainability among the five paths. The findings of this study contribute to the role of Education 4.0's innovative learning skills in improving high school students' learning sustainability in the UAE, providing actionable insights for educational policymakers and practitioners.